A phrase table without phrases: Rank encoding for better phrase table Compression - Junczys-Dowmunt, Marcin (Proceedings of the 16th Annual Conference of the European Association for Machine Translation, 2012)
This paper describes the first steps towards a minimum-size phrase table implementation to be used for phrase-based statistical machine translation. The focus lies on the size reduction of target language data in a phrase table. Rank Encoding (R-Enc), a novel method for the compression of word-aligned target language in phrase tables is presented. Combined with Huffman coding a relative size reduction of 56 percent for target phrase words and alignment data is achieved when compared to bare Huffman coding without R-Enc. In the context of the complete phrase table the size reduction is 22 percent.